The practice of engineering management in Saudi Arabia - Alidi, A.S. (1991)
The practice of engineering management (EM) in Saudi Arabia (SA) is assessed by reviewing the evolution of EM and the status of EM education in the country. A special survey design has been developed to find the extent of EM practice in major SA industrial organizations. The results of the survey, the status of local associations that implement and promote EM, and the existence of both engineering and management programs at SA universities are used as indicators of the current status of the practice of EM in SA. Additionally, the results of this study can be used to assess the need for establishing EM programs at SA universities. Finally, recommendations on enhancing the practice of EM in SA are presented